RANCANG BANGUN RANGKA MESIN INKUBATOR PENETAS TELUR KAPASITAS 50 BUTIR OTOMATIS BERTENAGA (HYBRID) - Aldiansyah, Hendri; Ginting, Edison (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
One such innovation is the hybrid-powered egg incubator, an innovative device that utilizes two energy sources, typically a combination of electricity and alternative energy such as solar power or batteries, to create optimal conditions for hatching poultry eggs. This hybrid system is designed to maintain the stability of temperature, humidity, and ventilation necessary for embryo development, especially in areas that frequently experience power outages or have limited access to conventional power grids. The primary advantage of a hybrid-powered egg incubator is its flexibility and reliability in unstable energy conditions. This system ensures that the hatching process continues even in the event of power supply disruptions, thereby increasing the chances of successful hatching. Additionally, the use of alternative energy can reduce operational costs and environmental impact. This hybrid incubator is ideal for farmers in remote areas, projects aimed at conserving rare bird species, or for small to medium-scale operations looking to improve efficiency and sustainability in the hatching process.